The wrongful conviction of indigenous people in Australia and Canada - Roach, Kent (Flinders Law Journal, 2020)
Drawing on Rachel Dioso-Villa''s repository of wrongful convictions published in this issue, this article examines known cases of wrongful convictions of Indigenous persons in Australia and Canada. It finds that Indigenous people are over-represented among the wrongfully convicted in relation to their representation in the population in both Australia and Canada. At the same time, there are likely many undiscovered wrongful convictions of Indigenous persons especially when the over-representation of Indigenous men and women in prison is considered. A factor in this likely under-representation of Indigenous people among remedied wrongful convictions may be the incentives that accused, especially Indigenous women, face to plead guilty even if they are not guilty. This finding underlines some of the dangers of limiting wrongful convictions to cases of proven factual innocence and not including among the wrongfully convicted those who may have valid defences such as self-defence.